"Being uncomfortable is important": the potential of study abroad for preservice English teachers. (3rd April 2019) - Shoffner, Melanie
ABSTRACT: Study abroad programs offer undergraduate students multiple benefits by providing academic, professional and personal learning experiences that cannot be fully replicated in the domestic university setting. Recognizing the unique positioning of preservice English teachers participating in a London summer study abroad program, the author created a qualitative study to explore the implications of the preservice teachers' experiences. This article begins by connecting the potential benefits of study abroad, generally, to preservice teachers, specifically. A description of the summer study abroad program in London is followed by an explanation of the qualitative study used to examine preservice English teachers' experiences in the program. Three themes are identified and discussed – personal independence, engagement in learning and pedagogical connection – as well as the implications of the independence, engagement and connection developed during study abroad when the preservice teachers enter the classroom as secondary English teachers.